2006
DOI: 10.5194/npg-13-577-2006
|View full text |Cite
|
Sign up to set email alerts
|

An efficient nonlinear cardinal B-spline model for high tide forecasts at the Venice Lagoon

Abstract: Abstract. An efficient class of nonlinear models, constructed using cardinal B-spline (CBS) basis functions, are proposed for high tide forecasts at the Venice lagoon. Accurate short term predictions of high tides in the lagoon can easily be calculated using the proposed CBS models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Sobey (2006) shown that the normal mode decomposition approach is a useful analysis methodology in the evaluation of storm tide and tsunami hazard at a coastal site. During the last years, the techniques based on wavelet decompositions (Ró _ zyński and Reeve 2005), cardinal B-spline basic functions (Wei and Billings 2006), artificial neural networks (Chang and Lin 2006) were used in the investigations of water level variations at different time scales. Among these methods, the chaotic time series analysis of water level occupies a fitting place.…”
Section: Introductionmentioning
confidence: 99%
“…Sobey (2006) shown that the normal mode decomposition approach is a useful analysis methodology in the evaluation of storm tide and tsunami hazard at a coastal site. During the last years, the techniques based on wavelet decompositions (Ró _ zyński and Reeve 2005), cardinal B-spline basic functions (Wei and Billings 2006), artificial neural networks (Chang and Lin 2006) were used in the investigations of water level variations at different time scales. Among these methods, the chaotic time series analysis of water level occupies a fitting place.…”
Section: Introductionmentioning
confidence: 99%
“…are given in Table 1 ( Wei and Billings, 2006b). For detailed discussions on cardinal B-splines and the associated wavelets, see Chui (1992).…”
Section: The Multi-wavelet Basis Functionsmentioning
confidence: 99%
“…For example, cardinal B-splines are an important class of basis functions and can be used for multi-resolution wavelet decompositions (Ahuja, Lertrattanapanich, & Bose, 2005). The B-spline function of mth order can be computed recursively according to de Boor (1978) and Chui and Wang (1992), and several low-order B-spline functions are provided in Wei and Billings (2006). Then the φ m l (·) can be expressed from the mth-order Bspline (B m ) with the scale j and shift indices l:…”
Section: Identification Of a Tv-narx Modelmentioning
confidence: 99%